Unconsciously Influential. Understanding sociotechnical Influence on social media - Hogsnes, Mathilde; Tor-Morten Grønli; Hansen, Kjeld (Scandinavian journal of information systems, 2023)
Over the last two decades, the rise of social media platforms such as Instagram, YouTube, and TikTok has sparked a global shift in commercial practices worldwide. People are exposed to and influenced by massive amounts of commercial content carefully and strategically integrated into these platforms’ social content. In addition, due to network structures, people’s engagement in the form of likes, comments, and simply viewing content results in the influence of people within and outside their network. In this study, we adopt a sociotechnical perspective and study the interplay between social and technical components in how influence is exercised on social media. Specifically, we identify the actors involved in the influence of commercial content and analyse how they exercise their influence for commercial purposes. Based on our findings and analysis, we present three contributions to Information systems literature: (1) how people have become unconsciously influential in spreading commercial content, which is the premise for social media commercial success, (2) how people’s social and commercial lives and contents are increasingly intertwined and (3) how this interweaving effect removes peoples’ ability to reflect on the content they engage with critically. Our study draws attention to the societal outcomes caused by technologies in practice.